2002
DOI: 10.1080/14616730210123102
|View full text |Cite
|
Sign up to set email alerts
|

Adult attachment and preparing to provide care for older relatives

Abstract: A normative developmental task of middle-aged adults is to consider older family members' care needs. Preparing for future caregiving responsibilities may be an important way to prevent excessive stress responses when the caregiver role is taken on. The present study investigates the extent to which attachment style and dimensions of attachment insecurity predict whether middle-generation adults prepare for possible future caregiving responsibilities, feel prepared for these responsibilities and are satisfied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
3
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 59 publications
1
33
3
3
Order By: Relevance
“…Previous research has shown that attachment is significantly related to perceived burden (Carpenter, 2001;Cicirelli, 1993;Crispi, Schiaffino, & Berman, 1997;Karantzas, Evans, & Foddy, 2010), perceived symptoms (Monin, Schulz, & Kershaw, 2013), well-being (Perren, Schmid, Herrmann, & Wettstein, 2007), feelings of preparedness to and satisfaction with providing care (Sorensen, Webster, & Roggman, 2002), and willingness to provide care (Feeney & Hohaus, 2001;Karantzas et al, 2010). In all of these studies secure attachment is consistently associated with more positive outcomes.…”
Section: Adult Attachmentmentioning
confidence: 93%
“…Previous research has shown that attachment is significantly related to perceived burden (Carpenter, 2001;Cicirelli, 1993;Crispi, Schiaffino, & Berman, 1997;Karantzas, Evans, & Foddy, 2010), perceived symptoms (Monin, Schulz, & Kershaw, 2013), well-being (Perren, Schmid, Herrmann, & Wettstein, 2007), feelings of preparedness to and satisfaction with providing care (Sorensen, Webster, & Roggman, 2002), and willingness to provide care (Feeney & Hohaus, 2001;Karantzas et al, 2010). In all of these studies secure attachment is consistently associated with more positive outcomes.…”
Section: Adult Attachmentmentioning
confidence: 93%
“…Negative model of self (attachment anxiety) has been related to feeling less prepared (Sörensen, Webster, & Roggman, 2002), providing less care (Carpenter, 2001; Cicirelli, 1993; Feeney & Collins, 2001; Kim & Carver, 2007), less responsiveness (Daire, 2002; Ingebretsen & Solem, 1998; Markiewicz, Reis, & Gold, 1997), and more caregiver burden (Carpenter, 2001; Cicirelli, 1993; Crispi, Schiaffino, & Berman, 1997). Among spousal caregivers, the frequency of caregiving may be a function of both attachment and gender, with negative model of self and male gender related to less caregiving (Kim & Carver, 2007).…”
Section: Negative Model Of Self and Caregivingmentioning
confidence: 99%
“…Empirical studies have indicated that middle-aged children's feelings of attachment were directly associated with their feelings of preparedness for future caregiving of parents (So¨rensen et al 2002) and with their commitment to help their parents in the future, while the relation to present support was mediated by the adult children's frequency of contact (Cicirelli 1983). Middleaged daughters' secure attachment to their elderly mothers (as well as their feelings of obligation) were positively associated with the time the daughters invested in instrumental support for their mothers (Cicirelli 1993).…”
Section: Attachment and Providing Supportmentioning
confidence: 99%